Effects of sacubitril/valsartan in ESRD patients undergoing hemodialysis with HFpEF - Guo, Yanhong; Ren, Mingjing; Wang, Tingting; Wang, Yulin; Pu, Tian; Li, Xiaodan; Yu, Lu; Wang, Liuwei; Liu, Peipei; Tang, Lin (Frontiers in Cardiovascular Medicine, 2022)
Introduction Heart failure with preserved ejection fraction (HFpEF), which is a common co-morbidity in patients with maintenance hemodialysis (MHD), results in substantial mortality and morbidity. However, there are still no effective therapeutic drugs available for HFpEF currently. Sacubitril/valsartan has been shown to significantly improve clinical outcomes and reverse myocardial remodeling among patients with heart failure with reduced ejection fraction (HFrEF). The effect of sacubitril/valsartan in MHD patients with HFpEF remains unclear. Our study was designed to assess the efficacy and safety of sacubitril/valsartan in MHD patients with HFpEF. Methods A total of 247 MHD patients with HFpEF treated with sacubitril/valsartan were included in this retrospective study. Patients were followed up regularly after medication treatment. The alterations in clinical, biochemical, and echocardiographic parameters before and after taking sacubitril/valsartan were collected. In addition, the safety of the sacubitril/valsartan treatment was also assessed. Among those 247 patients with MHD, 211 patients were already in treatment with angiotensin converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARBs) before being treated with sacubitril/valsartan. We also performed an analysis to compare the differences between the 211 patients who had previously received ACEi/ARB treatment and the 36 patients who were sacubitril/valsartan naive. Results Among those 247 patients with MHD, compared with baseline levels, systolic blood pressure (BP) (149.7 ± 23.6 vs. 137.2 ± 21.0 mmHg, P < 0.001), diastolic BP (90.2 ± 16.1 vs. 84.5 ± 14.1 mmHg, P < 0.001), heart rate (83.5 ± 12.5 vs. 80.0 ± 8.7 bpm, P < 0.001), N-terminal B-type natriuretic peptide precursor (NT-proBNP) [29125.0 (11474.5, 68532.0) vs. 12561.3 (4035.0, 37575.0) pg/ml, P < 0.001], and cardiac troponin I [0.044 (0.025, 0.078) vs. 0.0370 (0.020, 0.064) μg/L, P = 0.009] were markedly decreased after treatment with sacubitril/valsartan. New York Heart Association (NYHA) functional class showed a notable trend of improvement after 3–12 months of follow-up. Echocardiographic parameters including left ventricular posterior wall thickness (LVPWT) (11.8 ± 2.0 vs. 10.8 ± 1.9 mm, P < 0.001), intraventricular septal thickness in diastole (11.8 ± 2.0 vs. 11.2 ± 2.0 mm, P < 0.001), left ventricular end-diastolic diameter (53.8 ± 6.9 vs. 51.2 ± 7.1 mm, P < 0.001), left atrial diameter (LAD) (40.5 ± 6.2 vs. 37.2 ± 7.2 mm, P < 0.001), left ventricular end-diastolic volume (LVEDV) [143.0 (111.5, 174.0) vs. 130.0 (105.0, 163.0) ml, P < 0.001], left ventricular end-systolic volume (LVESV) [57.0 (43.0, 82.5) vs. 48.0 (38.0, 74.0) ml, P < 0.001], and pulmonary arterial systolic pressure [39.0 (30.5, 50.0) vs. 28.0 (21.0, 37.5) mmHg, P < 0.001] were significantly reduced after initiating the treatment of sacubitril/valsartan. The parameters of left ventricular diastolic function including E/A ratio [0.8 (0.7, 1.3) vs. 0.9 (0.8, 1.3), P = 0.008], maximal tricuspid regurgitation velocity [2.7 (2.5, 3.2) vs. 2.4 (2.0, 2.8) m/s, P < 0.001], septal e’wave velocity (8.0 ± 0.6 vs. 8.2 ± 0.5 cm/s, P = 0.001), lateral e’ wave velocity (9.9 ± 0.8 vs. 10.2 ± 0.7 cm/s, P < 0.001), E/e’ [8.3 (6.4, 11.8) vs. 7.2 (6.1, 8.9), P < 0.001], and left atrial volume index (37.9 ± 4.2 vs. 36.4 ± 4.1 ml/m2, P < 0.001) were significantly improved by sacubitril/valsartan. Among 211 patients who were already in treatment with ACEi/ARB and 36 patients who were sacubitril/valsartan naive, the improvement of cardiac function demonstrated by clinical outcomes and echocardiographic parameters were similar to the previous one of the 247 MHD patients with HFpEF. During the follow-up, none of the patients showed severe adverse drug reactions. Conclusion Our study suggested that sacubitril/valsartan treatment in MHD patients with HFpEF was effective and safe.